2020
DOI: 10.1038/s41420-020-0282-3
|View full text |Cite
|
Sign up to set email alerts
|

Expression profiling of microRNAs and isomiRs in conventional central chondrosarcoma

Abstract: Conventional central chondrosarcoma (CCC) is a malignant bone tumor that is characterized by the production of chondroid tissue. Since radiation therapy and chemotherapy have limited effects on CCC, treatment of most patients depends on surgical resection. This study aimed to identify the expression profiles of microRNAs (miRNAs) and isomiRs in CCC tissues to highlight their possible participation to the regulation of pathways critical for the formation and growth of this type of tumor. Our study analyzed miRN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 62 publications
(60 reference statements)
0
9
0
Order By: Relevance
“…Parafioriti et al [ 139 ] performed miRNoma profiling in chondrosarcoma tissues and identified several differentially expressed miRNAs and isomiRs in grade II-III compared with grade I samples. Analyzing predicted target genes, particularly for 5′ end isoforms, the authors observed that many of the pathways targeted by these isomiRs were involved in cancer-associated signaling, also suggesting a synergistic role with the canonical counterparts.…”
Section: Isomirs In Cancermentioning
confidence: 99%
“…Parafioriti et al [ 139 ] performed miRNoma profiling in chondrosarcoma tissues and identified several differentially expressed miRNAs and isomiRs in grade II-III compared with grade I samples. Analyzing predicted target genes, particularly for 5′ end isoforms, the authors observed that many of the pathways targeted by these isomiRs were involved in cancer-associated signaling, also suggesting a synergistic role with the canonical counterparts.…”
Section: Isomirs In Cancermentioning
confidence: 99%
“…IsomiRs have been associated with several human diseases such as pre-eclampsia [ 106 ], Huntington disease [ 107 ], Alzheimer’s disease [ 108 ], osteoarthritis [ 109 ], cardiovascular diseases [ 110 ], rheumatoid arthritis [ 111 ], and found to respond to bacterial infection [ 112 ]. Specific isomiR expression patterns have been observed in various cancer types [ 113 , 114 ] suggesting the miRNA-mediated level of regulation of tumorigenesis. In gastric cancer, several mature miRNAs generated from the two different arms (5p or 3p) of the same pre-miRNA exhibit reversed expression preferences (normal vs. cancer tissue) [ 115 ].…”
Section: Isomirs—a Limitless Source Of Potentially Novel Biomarkermentioning
confidence: 99%
“…Furthermore, the combination of isomiR features with state-of-the-art algorithms effectively differentiated normal from cancer cell lines [ 118 , 122 ]. Mature miRNAs and their isomiR variants, along with their target pathways, should be considered during tumor diagnosis, progression and treatment monitoring [ 114 ].…”
Section: Isomirs—a Limitless Source Of Potentially Novel Biomarkermentioning
confidence: 99%
“…Interestingly, it has been shown that alteration in isomiR profiles (rather than overall miRNA abundance) correlates with cancer progression, which suggests a unique role for isomiRs in tumorigenesis [22,23] . Multiple reports suggest that isomiRs can be used as biomarkers for tumor detection, classification and patients prognosis [24][25][26][27] . These observations highlight the importance of having computational tools to analyze isomiR expression profiles from sequencing data to further investigate their functions.…”
Section: Introductionmentioning
confidence: 99%